Investigating User Experience of an Immersive Virtual Reality Simulation Based on a Gesture-Based User Interface - Laine, Teemu H.; Suk, Hae Jung (Applied Sciences (Switzerland), 2024)
Featured Application: The results of this work can be applied to the design, implementation, and evaluation of immersive virtual reality experiences that utilize gesture-based user interfaces. The affordability of equipment and availability of development tools have made immersive virtual reality (VR) popular across research fields. Gesture-based user interface has emerged as an alternative method to handheld controllers to interact with the virtual world using hand gestures. Moreover, a common goal for many VR applications is to elicit a sense of presence in users. Previous research has identified many factors that facilitate the evocation of presence in users of immersive VR applications. We investigated the user experience of Four Seasons, an immersive virtual reality simulation where the user interacts with a natural environment and animals with their hands using a gesture-based user interface (UI). We conducted a mixed-method user experience evaluation with 21 Korean adults (14 males, 7 females) who played Four Seasons. The participants filled in a questionnaire and answered interview questions regarding presence and experience with the gesture-based UI. The questionnaire results indicated high ratings for presence and gesture-based UI, with some issues related to the realism of interaction and lack of sensory feedback. By analyzing the interview responses, we identified 23 potential presence factors and proposed a classification for organizing presence factors based on the internal–external and dynamic–static dimensions. Finally, we derived a set of design principles based on the potential presence factors and demonstrated their usefulness for the heuristic evaluation of existing gesture-based immersive VR experiences. The results of this study can be used for designing and evaluating presence-evoking gesture-based VR experiences.
Keywords: gesture-based interface; immersive virtual reality; mixed-method user study; presence; user experience